2019
DOI: 10.1007/978-3-030-30048-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Instance Generation via Generator Instances

Abstract: Access to good benchmark instances is always desirable when developing new algorithms, new constraint models, or when comparing existing ones. Handwritten instances are of limited utility and are timeconsuming to produce. A common method for generating instances is constructing special purpose programs for each class of problems. This can be better than manually producing instances, but developing such instance generators also has drawbacks. In this paper, we present a method for generating graded instances co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Most studies in this area tackle one problem class at a time. We here extend [1] to automatically produce instances for any problem class. The goal is to automate finding instances that are particularly suited to one algorithm but not another, and to study characteristics of these instances.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies in this area tackle one problem class at a time. We here extend [1] to automatically produce instances for any problem class. The goal is to automate finding instances that are particularly suited to one algorithm but not another, and to study characteristics of these instances.…”
Section: Related Workmentioning
confidence: 99%
“…When developing a model of a combinatorial problem class, a set of representative instances drawn from the class is essential for evaluating the model's performance. Recently, Akgn et al [1] demonstrated how to generate instances automatically from the Essence 1 specification of a problem class [10]. The instances generated are graded : neither too difficult nor too easy relative to a given solver and resource limits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the moment the instance generator has to be manually created, and is the only part of the whole system that is not automated. However, this issue has been tackled in a recent work [2] within the same pipeline, which can be integrated into our system in the future. To keep the computational cost manageable, we require a set of relatively easy (but not trivial) instances for the training phase, which we define as solvable by MINION [19] on an unstreamlined model within a time limit of [10, 300] seconds.…”
Section: Generating Diverse Training Instancesmentioning
confidence: 99%